A composite hydroxyapatite coating that promotes osteogenesis and is antibacterial

By preparing composite hydroxyapatite coatings doped with SiO2, Gd2O3 and CeO2 on the surface of titanium implants, the shortcomings of the surface composite coatings of titanium implants in the prior art in terms of osteoinductivity and antibacterial properties are solved, and better osteointegration and antibacterial effects are achieved.

CN116510081BActive Publication Date: 2025-04-25SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310500773.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-04-25
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

Existing surface composite hydroxyapatite coatings of existing titanium implants have insufficient osteoinductivity and antibacterial properties, resulting in insufficient binding of the implant to bone tissue and a high risk of bacterial infection.

Method used

A composite hydroxyapatite coating was prepared by plasma spraying technology on the surface of the titanium implant, and silica, gadolinium trioxide and ceria nanoparticles were added to form a composite powder with a micro-nano structure.

Benefits of technology

This composite coating significantly improves the antibacterial and osteogenic properties of the implant, enhances the bone integration ability and prevents bacterial infection, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116510081B_ABST
    Figure CN116510081B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of advanced biomaterials, and provides a composite hydroxyapatite coating that can promote osteogenesis and resist bacteria, which is prepared from the following raw materials in mass percentage: 93% to 98% HA, 1% to 3% SiO2NP, 0.5% to 2% Gd2O3NP, 0.5% to 2% CeO2NP, and the sum of the mass percentages of each raw material is 100%. The present invention incorporates silicon dioxide (SiO2), gadolinium trioxide (Gd2O3) and cerium dioxide (CeO2) nanoparticles into micron-sized hydroxyapatite powder to form a hydroxyapatite composite powder with a micro-nano structure, and then prepares a composite hydroxyapatite coating (HASiGdCe) on the surface of a titanium implant by plasma spraying technology. Experiments have shown that the composite coating takes into account both antibacterial and osteogenesis, can effectively enhance implant bone integration and prevent bacterial infection, and has broad application prospects in the treatment of bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced biomaterials, and particularly relates to a preparation method and application of a composite hydroxyapatite coating on the surface of a titanium implant. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Titanium metal and alloys are widely used as artificial implants for hard tissue repair and joint replacement due to their excellent mechanical strength, corrosion resistance, fatigue resistance and biocompatibility. However, the biological inertness and stress shielding effect of titanium implants make their osteoconductivity and osteoinductivity poor, which often leads to insufficient bonding with bone tissue. In addition, the surface of titanium implants lacks antibacterial properties and is prone to bacterial infection or biofilm formation, which is also an important reason for their implant failure. It has been reported that about 18% of the causes of implant failure are due to aseptic loosening caused by insufficient bonding between the implant and bone tissue, while 20% of the failures are attributed to bacterial infection, and some are due to both. Therefore, it is necessary to develop an implant that takes into account both antibacterial and osteogenic properties.

[0004] An effective way to deal with the stress shielding effect and biological inertness of titanium is to apply an osteoconductive coating on its surface to enhance its ability to bind to bone tissue. Hydroxyapatite (HA), which is mainly composed of calcium and phosphate minerals, is widely used as a coating material for metal implants because of its bioactivity and osteoconductivity similar to that of natural human bones. Hydroxyapatite coating inherits the excellent mechanical properties and corrosion resistance of titanium, and can promote the bonding between implants and bone tissue and support the uniform ingrowth of bones. Coating technologies such as plasma spraying, pulsed laser deposition, laser cladding, biomimetic solution method, electrophoretic deposition, sol-gel method and magnetron sputtering deposition have been reported to successfully prepare hydroxyapatite coatings on titanium surfaces. Plasma spray coating has the advantages of good bonding strength, high deposition rate, low cost, low pollution and variable coating thickness, and is the only commercial coating method widely used for orthopedic implants.

[0005] At present, there are many methods to modify hydroxyapatite coatings using various dopants, but the prepared composite coatings cannot yet have both excellent osteoinductivity and antibacterial properties, which limits their further application. Summary of the invention

[0006] An effective way to solve the problem of insufficient osteoinductivity and antibacterial properties of hydroxyapatite coatings is to add some dopants that can play a specific function to hydroxyapatite. Oxides of some functional elements acting as dopants can often produce special effects, greatly improving the performance of hydroxyapatite coatings. Therefore, in order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a preparation method and application of a composite hydroxyapatite coating on the surface of an implant. The present invention incorporates silicon dioxide (SiO2), gadolinium trioxide (Gd2O3) and cerium dioxide (CeO2) nanoparticles into micron-sized hydroxyapatite powder to form a hydroxyapatite composite powder with a micro-nano structure, and then prepares a composite hydroxyapatite coating (HASiGdCe) on the surface of a titanium implant by plasma spraying technology. Experiments have shown that the composite coating takes into account both antibacterial and osteogenic properties, can effectively enhance implant bone integration and prevent bacterial infection, and has broad application prospects in the treatment of bone defects.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a composite hydroxyapatite coating that can promote osteogenesis and is antibacterial, which is prepared from the following raw materials in mass percentage: 93% to 98% HA, 1% to 3% SiO2 NP, 0.5% to 2% Gd2O3 NP, and 0.5% to 2% CeO2 NP, and the sum of the mass percentages of the raw materials is 100%.

[0009] The second aspect of the present invention provides a plasma spraying method for preparing a composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria, comprising:

[0010] HA, SiO2, Gd2O3 and CeO2 are uniformly mixed, wet ball-milled and dried to obtain HASiGdCe powder with a micro-nano composite structure;

[0011] Cleaning and roughening the surface of the pure titanium substrate to obtain a pretreated substrate;

[0012] The HASiGdCe powder is sprayed on the pretreated substrate surface by plasma spraying to form a HA-based biological coating.

[0013] The third aspect of the present invention provides the use of the above-mentioned composite hydroxyapatite coating in the preparation of artificial implants.

[0014] Beneficial effects of the present invention

[0015] (1) The present invention successfully prepared a hydroxyapatite coating (HASiGdCe) doped with SiO2 NP, Gd2O3NP and CeO2 NP on the titanium surface through plasma spraying technology. The HASiGdCe coating has a micron-level surface roughness, provides a large surface area for new bone formation, has a positive effect on cell behavior, and is beneficial to enhance the bone fusion of the implant. The antibacterial rates of the HASiGdCe coating against Staphylococcus aureus and Pseudomonas aeruginosa are 67.12142% and 71.0075%, respectively. This shows that the HASiGdCe coating has excellent antibacterial properties and may have a strong antibacterial effect on both Gram-positive and Gram-negative bacteria. Through CCK-8 assay and ALP activity detection, it was found that compared with the HA coating, the HASiGdCe coating has more excellent biocompatibility and osteogenic properties.

[0016] (2) In order to make the prepared composite coating have better performance in terms of antibacterial and osteogenic properties, the present invention has conducted long-term research and experimental exploration on the action mechanism of dopants with different functions, and found that: compared with HASi, HASiGd has increased ALP activity and antibacterial properties, indicating that Gd2O3 NPs can promote osteogenesis and antibacterial properties. Compared with HASiGd, HASiGdCe has increased ALP activity and antibacterial properties, indicating that CeO2 NPs can promote osteogenesis and antibacterial properties. Figure 3 , Figure 5 The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 : Microscopic characteristics of the composite powder prepared in Example 1 of the present invention.

[0019] Figure 2 :Surface characteristics of the composite coating prepared in Example 1 of the present invention.

[0020] Figure 3 : Antibacterial properties of the composite coating of the present invention.

[0021] Figure 4 :Evaluation results of cell activity of the composite coating of the present invention.

[0022] Figure 5 : Evaluation results of ALP activity of the composite coating of the present invention. DETAILED DESCRIPTION

[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0024] A composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria is prepared from the following raw materials in mass percentage: 93% to 98% HA, 1% to 3% SiO2 NP, 0.5% to 2% Gd2O3 NP, and 0.5% to 2% CeO2 NP, wherein the sum of the mass percentages of the raw materials is 100%.

[0025] In some embodiments, the HA is micrometer-sized.

[0026] A plasma spraying preparation method of a composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria, comprising:

[0027] HA, SiO2, Gd2O3 and CeO2 are uniformly mixed, wet ball-milled and dried to obtain HASiGdCe powder with a micro-nano composite structure;

[0028] Cleaning and roughening the surface of the pure titanium substrate to obtain a pretreated substrate;

[0029] The HASiGdCe powder is sprayed on the pretreated substrate surface by a plasma spraying method to form a HA-based biological coating.

[0030] In some embodiments, the wet ball milling uses anhydrous ethanol solution, the rotation speed is set to 180-200 r / min, and the ball milling time is 8-10 min.

[0031] Specifically, the wet ball milling process conditions are as follows: In order to ensure the stability of powder feeding and to make the components of the composite powder evenly mixed, a QM-QX4L ball mill is used for mechanical ball milling and powder mixing. First, according to the powder ratio of the material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the required mass of powder and stainless steel grinding balls twice the total mass of the powder. Then the powder to be mixed and the stainless steel balls are placed in a clean and dry ball mill, and an appropriate amount of anhydrous ethanol solution is added. The ball mill speed is set to 180r / min, and the ball milling time is 10min.

[0032] In some embodiments, the specific conditions for drying are drying at 80° C. to 90° C. for more than 3 hours.

[0033] Specifically, after the ball milling is completed, the slurry is poured into a clean tray and placed in a vacuum drying oven to dry for 3 hours at 80° C. Finally, the dried powder and the stainless steel balls are separated by sieving to obtain the desired composite powder.

[0034] In some embodiments, the specific cleaning method is anhydrous ethanol ultrasonic cleaning.

[0035] In some embodiments, the specific method of the surface roughening treatment is sandblasting.

[0036] In some embodiments, the plasma spraying process conditions are: the plasma spraying process conditions are voltage 65-70V, current 550-560A, powder feeding rate 13-15g / min, spray gun speed 100-110mm / s, spraying distance 120-130mm, and spraying pass distance 3-4mm.

[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0038] Example 1

[0039] 1. Materials required for synthesis:

[0040] Micrometer-sized hydroxyapatite (HA) (Dulai, China), silica nanoparticles (SiO2 NPs) (Macklin, China), gadolinium trioxide nanoparticles (Gd2O3 NPs) (Desheng, China) and cerium dioxide nanoparticles (CeO2NPs) (Macklin, China).

[0041] 2. Methods

[0042] 2.1 Preparation of composite hydroxyapatite powder and coating

[0043] The invention provides a HASiGdCe biological coating, which is prepared from the following raw materials in mass percentage: 96% HA, 2% SiO2 NP, 1% Gd2O3 NP, and 1% CeO2 NP.

[0044] The present invention provides a plasma spraying preparation method of a HASiGdCe bio-coating, comprising:

[0045] HA, SiO2, Gd2O3, and CeO2 are mixed evenly to obtain composite powder. In order to ensure the stability of powder feeding and mix the components of the composite powder evenly, a QM-QX4L ball mill is used for mechanical ball milling and powder mixing. First, according to the powder ratio of the material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the required mass of powder and stainless steel grinding balls twice the total mass of the powder. Then put the powder to be mixed and the stainless steel balls into a clean and dry ball mill, and add an appropriate amount of anhydrous ethanol solution. The ball mill speed is set to 180r / min, and the ball milling time is 10min. After the ball milling is completed, the slurry is poured into a clean tray and placed in a vacuum drying oven, and dried at 80℃ for 3h. Finally, the dried powder and stainless steel balls are sieved and separated to obtain HASiGdCe powder with a micro-nano composite structure;

[0046] The surface of the pure titanium substrate is cleaned (ultrasonic cleaning with anhydrous ethanol) and roughened (sandblasting) to obtain a pretreated substrate;

[0047] HASiGdCe powder was sprayed on the pretreated substrate surface by plasma spraying to form a HA-based bio-coating. The plasma spraying process conditions are shown in Table 1 below:

[0048] Table 1

[0049]

[0050] 2.2 Surface characteristics of powders and coatings

[0051] Field emission scanning electron microscopy (SEM, QUANTA FEG 250) and energy dispersive spectrometer (EDS, INCA X-MAX-50) were used to observe the microstructure and elemental composition of composite hydroxyapatite (HASiGdCe) powder and coating.

[0052] 2.3 Evaluation of in vitro antibacterial properties

[0053] The antibacterial properties of the composite hydroxyapatite (HASiGdCe) coating were verified using Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Pseudomonas aeruginosa (P. aeruginosa) as representative bacteria. 6 CFU / mL was inoculated on the coating surface and incubated for 24 hours. Afterwards, the attached bacteria on the different coating surfaces were eluted by ultrasonic treatment, and the eluate was diluted 10,000 times and then spread on LB agar plates. After incubation at 37 degrees Celsius for 24 hours, the colonies formed in each group were counted to calculate the antibacterial rate.

[0054] 2.4 Cell viability assay

[0055] The cell viability of osteoblasts on the composite hydroxyapatite coating surface was evaluated using the CCK8 assay. Briefly, MC3T3-E1 cells (mouse preosteoblasts) were cultured at 2 × 10 4 The density of cells / well was cultured on the coated surface for 3, 5 and 7 days. Then, α-MEM medium and CCK-8 reagent were mixed in a ratio of 10:1 and added to each well and incubated at 37°C in the dark for 2 hours. Subsequently, 100ul of the suspension was transferred to a 96-well plate and the absorbance was read at 450nm using a microplate reader.

[0056] 2.5 Osteogenesis performance assessment

[0057] In order to evaluate the effect of composite hydroxyapatite coating on the osteogenic performance of MC3T3-E1 cells, the present invention conducted ALP quantitative analysis. 4 The density of cells / well was inoculated on the coating surfaces of different groups. After culturing with osteogenic induction medium for 7 or 14 days, the ALP activity of cells in different groups was measured using an ALP assay kit (Beyotime, China).

[0058] Experimental results:

[0059] 1. Surface characteristics of powder and coating

[0060] The microstructure of composite hydroxyapatite (HASiGdCe) powder is shown in Figure 1 As shown, it can be found that the incorporated nanoparticles approximately uniformly wrap the hydroxyapatite powder to form a composite powder with a micro-nano structure.

[0061] The morphology of the composite hydroxyapatite coating is evenly distributed, showing the typical roughening characteristics of plasma spraying ( Figure 2 ). Nanoparticles have high temperature characteristics and fast cooling rate during plasma spraying, which can retain or re-form nanostructures, so the surface roughness of the coating is also increased. The composite coating has a micron-level surface roughness, which provides a large surface area for new bone formation, has a positive effect on cell behavior, and is conducive to enhancing implant bone fusion.

[0062] High-magnification images clearly show the presence of microcracks, holes, and solidified droplets in the coating caused by splashing droplets. The surface microcracks are caused by rapid quenching during plasma spraying. The holes can provide a high specific area for the subsequent nucleation of calcium phosphate and enhance the bonding strength. During the formation of the composite coating, the doped nanospheres are wrapped around the outside of the hydroxyapatite microspheres and flow to the solidified edge of the coarse particles as the droplets spread. Therefore, nanoparticles distributed on the edges of the flat coarse particles in the composite coating can be seen.

[0063] 2. Antibacterial performance test

[0064] The antibacterial properties of the composite hydroxyapatite (HASiGdCe) coating were verified using Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Pseudomonas aeruginosa (P. aeruginosa) as representative bacteria. Figure 3 As shown, the antibacterial rates of HASiGdCe coating against Staphylococcus aureus and Pseudomonas aeruginosa were 67.12142% and 71.0075%, respectively. This indicates that HASiGdCe coating has excellent antibacterial properties and may have a strong antibacterial effect on both Gram-positive and Gram-negative bacteria.

[0065] 3. Cell Viability

[0066] The present invention uses CCK-8 assay to evaluate the cell activity of osteoblasts on the surface of HASiGdCe coating. The CCK-8 assay results are as follows Figure 4 As shown in the figure, on the 3rd and 5th days, the cell activity of the HASiGdCe group was similar to that of the Ti group and HA. On the 7th day, the cell activity of the HASGdCe group was higher than that of the HA group and the Ti group. Therefore, the HASiGdCe coating has extremely excellent biocompatibility.

[0067] 4. Osteogenic Differentiation

[0068] The effect of HASiGdCe coating on osteogenic differentiation was evaluated by detecting the ALP activity of MC3T3-E1 cells. ALP activity is a signaling pathway for early osteogenic differentiation of preosteoblasts and Bone metabolism The quantitative results of ALP are as follows: Figure 4 As shown, the ALP activity of the HASiGdCe group was always higher than that of the HA group, whether at 4 or 7 days, indicating that the HASiGdCe coating has excellent osteogenic properties.

[0069] In this study, the present invention successfully prepared a hydroxyapatite coating (HASiGdCe) doped with SiO2NP, Gd2O3NP and CeO2NP on the titanium surface by plasma spraying technology. The HASiGdCe coating has a micron-level surface roughness, which provides a large surface area for new bone formation, has a positive effect on cell behavior, and is conducive to enhancing the bone fusion of the implant. The antibacterial rates of the HASiGdCe coating against Staphylococcus aureus and Pseudomonas aeruginosa are 67.12142% and 71.0075%, respectively. This shows that the HASiGdCe coating has excellent antibacterial properties and may have a strong antibacterial effect on both Gram-positive and Gram-negative bacteria. CCK-8 assay and ALP activity detection found that compared with the HA coating, the HASiGdCe coating has more excellent biocompatibility and osteogenic properties.

[0070] Example 2

[0071] The invention provides a HASiGdCe biological coating, which is prepared from the following raw materials in mass percentage: 93% HA, 3% SiO2 NP, 2% Gd2O3 NP, and 2% CeO2 NP, and the sum of the mass percentages of the raw materials is 100%.

[0072] The preparation method is the same as that in Example 1.

[0073] The test results show that the HASiGdCe coating prepared in this embodiment also has micron-level surface roughness, excellent antibacterial properties, and outstanding biocompatibility and osteogenic properties.

[0074] Example 3

[0075] The invention provides a HASiGdCe biological coating, which is prepared from the following raw materials in mass percentage: 98% HA, 1% SiO2 NP, 0.5% Gd2O3 NP, 0.5% CeO2 NP, and the sum of the mass percentages of the raw materials is 100%.

[0076] The preparation method is the same as that in Example 1.

[0077] The test results show that the HASiGdCe coating prepared in this embodiment also has micron-level surface roughness, excellent antibacterial properties, and outstanding biocompatibility and osteogenic properties.

[0078] Comparative Example 1

[0079] The HA coating was prepared by the method of Example 1 without adding a dopant.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that SiO2 NP is doped, and the amounts of HA and SiO2 NP are the same as in Example 1, to obtain a HASi coating.

[0082] Comparative Example 3

[0083] The difference from Example 1 is that SiO2 NP and Gd2O3 NP are doped, and the amounts of HA, SiO2 NP and Gd2O3 NP are the same as those in Example 1, so as to obtain a HASiGd coating.

[0084] like Figure 3 and Figure 5As shown in the figure, compared with HA coating, HASi coating had upregulated ALP activity and no significant difference in antibacterial activity, indicating that SiO2 NPs can promote osteogenesis and have no significant effect on antibacterial activity. Compared with HASi coating, HASiGd coating had upregulated ALP activity and antibacterial activity, indicating that Gd2O3 NPs can promote osteogenesis and antibacterial activity. Compared with HASiGd coating, HASiGdCe coating had upregulated ALP activity and antibacterial activity, indicating that CeO2 NPs can promote osteogenesis and antibacterial activity.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria, characterized in that: Prepared from the following raw materials in mass percentage: 93%~98% HA, 1%~3% SiO2 NP, 0.5%~2% Gd2O3 NP, 0.5%~2% CeO2 NP, the sum of the mass percentages of each raw material is 100%; The composite hydroxyapatite coating has a micron-level surface roughness.

2. The osteogenesis-promoting and antibacterial composite hydroxyapatite coating according to claim 1, characterized in that: The HA is in micron size.

3. A plasma spraying method for preparing the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 1, characterized in that: include: HA, SiO2, Gd2O3 and CeO2 are uniformly mixed, wet-milled and dried to obtain HASiGdCe powder with a micro-nano composite structure; Cleaning and roughening the surface of the pure titanium substrate to obtain a pretreated substrate; The HASiGdCe powder is sprayed on the pretreated substrate surface by plasma spraying to form a HA-based biological coating.

4. The plasma spraying preparation method of the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 3, characterized in that: The wet ball milling uses anhydrous ethanol solution, the rotation speed is set to 180-200 r / min, and the ball milling time is 8-10 min.

5. The plasma spraying method for preparing the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 3, characterized in that: The specific conditions of the drying are drying at 80° C. to 90° C. for more than 3 hours.

6. The plasma spraying method for preparing the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 3, characterized in that: The specific cleaning method is anhydrous ethanol ultrasonic cleaning.

7. The plasma spraying method for preparing the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 3, characterized in that: The specific method of the surface roughening treatment is sandblasting.

8. The plasma spraying method for preparing the composite hydroxyapatite coating capable of promoting osteogenesis and resisting bacteria as claimed in claim 3, characterized in that: The process conditions of plasma spraying are voltage 65~70 V, current 550~560A, powder feeding rate 13~15g / min, spray gun speed 100~110 mm / s, spray distance 120~130 mm, and spray pass distance 3~4 mm.

9. Use of the osteogenesis-promoting and antibacterial composite hydroxyapatite coating according to claim 1 or 2 in the preparation of artificial implants.